Marginalidade e melodrama no cinema brasileiro - Freitas, Rafael Fernandes de (2015)
Melodrama here is taken beyond a definition as theatrical or cinematic genre. From the concept of melodramatic imagination, by Peter Brooks, this study follows the main changes that led Europe from the Middle Ages to the capitalist world in order to present the foundations of a distinctive modern imagination whose mode of seeing the world is visual and fictionally translated in melodrama. Because of its far-reaching and massive presence in cultural production it is important to evaluate how melodrama represents reality; which treatment and valuation are given to certain topics and phenomena that daily takes our attention and interfere in our social and political existence. Under this perspective we develop a study on the representation of marginality from the aesthetic resources of the melodramatic imagination, which is based on the analysis of the films Pixote - a lei do mais fraco (1980) and Linha de Passe (2008).